Usability Analysis on the Ciamis Regency Communication and Information Service Website Using Heuristic Evaluation - Zamzamy, Dede Luthfi; Komariah, Shipa Khoerotul; Sidik R, Cecep Muhamad (Journal of Applied Information System and Informatic (JAISI), 2025)
The website of the Ciamis Regency Communication and Informatics Service (Diskominfo) has an important role in providing transparent and accurate information to the public, as well as a means of communication between the government and citizens. Usability problems can vary, ranging from unintuitive interface design, confusing navigation, to information that is difficult to find. This can have an impact on inadequate user experience, which in turn can reduce the effectiveness of the website as a medium for communication and information dissemination. The purpose of the usability analysis of the Ciamis Regency Communication and Informatics Service (Diskominfo) website is to improve the quality of the website, an evaluation of the usability aspects of the website is needed. One method used to identify usability problems in website development is Heuristic Evaluation. The evaluation results showed several usability problems in the aspects of System status visibility, Consistency and standards, Helping users recognize, diagnose, and recover from errors, Recognizing rather than remembering, Aesthetic and minimalist design. Based on these findings, it is recommended that the Ciamis Regency Diskominfo make improvements to the website design to improve the user experience. This study contributes to the development of a more user-friendly website design and increases efficiency in delivering information to the public.